Mechanical performance of collagen gels is dependent on purity, α1/α2 ratio, and telopeptides. Issue 1 (8th July 2021) - Slyker, Leigh; Diamantides, Nicole; Kim, Jongkil; Bonassar, Lawrence J.
Abstract: This article describes the compositional, mechanical, and structural differences between collagen gels fabricated from different sources and processing methods. Despite extensive use of collagen in the manufacturing of biomaterials and implants, there is little information as to the variation in properties based on collagen source or processing methods. As such, differences in purity and composition may affect gel structure and mechanical performance. Using mass spectrometry, we assessed protein composition of collagen from seven different sources. The mechanics and gelation kinetics of each gel were assessed through oscillatory shear rheology. Scanning electron microscopy enabled visualization of distinct differences in fiber morphology. Mechanics and gelation kinetics differed with source and processing method and were found to correlate with differences in composition. Gels fabricated from telopeptide‐containing collagens had higher storage modulus (144 vs. 54 Pa) and faster gelation (251 vs. 734 s) compared to atelocollagens, despite having lower purity (93.4 vs. 99.8%). For telopeptide‐containing collagens, as collagen purity increased, storage modulus increased and fiber diameter decreased. As α1/α2 chain ratio increased, fiber diameter increased and gelation slowed. As such, this study provides an examination of the effects of collagen processing on key quality attributes for use of collagen gels in biomedical contexts.